Alterations in gut–kidney axis indicators and TMAO-related biomarkers in elderly patients with hypertensive nephropathy - Li, Ziyi; Yang, Shi; Zhou, Xinyi; Qing, Yan; Zhang, Tiyan; Xu, Wenliu; Duan, Wei; Ren, Fajian; Deng, Hua; Wang, Wenjing; Li, Ming; Feng, Min; et al. (Frontiers in Medicine, 2025)
IntroductionGrowing evidence suggests that gut microbiota may influence renal function via the gut–kidney axis. This study assessed gut microbial composition, metabolic indicators, and inflammatory markers in elderly individuals with varying degrees of hypertensive kidney involvement.MethodsSeventy participants were stratified into three groups: healthy controls, hypertensive without renal impairment, and hypertensive with chronic kidney disease.ResultsThe chronic kidney disease group exhibited elevated serum urea and creatinine and reduced eGFR, along with increased levels of KIM-1, NGAL, IL-18, TNF-α, IL-6, NF-κB, and FMO3. Urinary TMAO was significantly decreased in both hypertensive groups, while serum TMAO remained unchanged. Although α- and β-diversity indices were comparable across groups, compositional shifts were noted, including higher relative abundance of Escherichia–Shigella and Haemophilus and lower levels of Faecalibacterium. Correlation analyses revealed associations between specific genera and host metabolic or inflammatory markers, such as a positive correlation between Enterobacter and urinary TMAO, and inverse correlations between Veillonella and both eGFR and urinary TMAO. Functional prediction indicated increased amino acid metabolism in the chronic kidney disease group.DiscussionThese findings suggest interrelated patterns involving gut microbial composition, toxin handling, and inflammatory status in elderly hypertensive individuals, supporting further investigation into microbiota-associated biomarkers within the framework of the gut–kidney axis.